PENGARUH APLIKASI KOMPOS JERAMI PADI DAN TITHONIA (KOJETO) TERHADAP SIFAT KIMIA PSAMENT - Febria Fitri; G Gusnidar; J Juniarti (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
Psament is a soil that has a low fertility rate which is characterized by low organic matter content (BO) so there are less water and nutrients available. Utilization of Psament for agricultural development must first be improved through other inputs such as BO and lime. This study aims to look at the interaction between KOJETO types and KOJETO doses on the chemical properties of Psament, to look at the effect of KOJETO types on the chemical properties of Psament, and to look at the effect of increasing KOJETO doses on the chemical properties of Psament. This research was conducted at the Wire House and Soil Laboratory of the Faculty of Agriculture, Andalas University, Padang. The experiment was designed according to a Factorial Randomized Complete Design with 2 factors and 3 replications. The main factor was the type of KOJETO which consisted of KOJETO A (0.75 PB Recommendations); KOJETO B (1 PB recommendation); KOJETO C (1.5 PB Recommendations). The second factor was KOJETO dose which consisted of (2.5, 5.0, 7.5, and 10.0) t ha-1. The results showed that the type of KOJETO with several doses interacted to increase the chemical properties of Psament with the highest value in the KOJETO C treatment with a dose of 10.0 t ha-1 namely N-total content of 0.34 %, CEC 15.87 cmol kg-1, Cadd 1,27 cmol kg-1 and Mgdd 0.69 cmol kg-1. The application of KOJETO C yielded the highest values of C-organic 2.80 %, Kdd 0.53 cmol kg-1 and Nadd 0.51 cmol kg-1. The single effect of increasing dose with the highest values at 10 t ha-1 were soil pH 5.80, P-available 14.59 ppm, C-organic 2.89 %, Kdd 0.52 cmol kg-1 and Nadd 0.50 cmol kg-1.